Using Mixed Methods with Multiple Stakeholders to Inform Development of a Breast Cancer Screening Decision Aid for Women with Limited Health Literacy. (15th September 2021) - Gunn, Christine; Maschke, Ariel; Paasche‐Orlow, Michael; Kressin, Nancy; Schonberg, Mara; Battaglia, Tracy
Abstract : Research Objective: Little is known about the best process for selecting content for decision aids (DAs) on mammography screening. This analysis triangulates perspectives (experts, primary care providers, and patients) to understand areas of divergent and convergent input across stakeholder groups in developing a breast cancer screening DA for women ages 40–54 with limited health literacy. Study Design: A 3‐round modified Delphi panel was conducted among national breast cancer screening and decision science experts. They rated the importance of 57 statements for possible inclusion in a breast cancer screening DA. Qualitative comments about each statement were collected via open‐ended text fields. Analysis was conducted following the RAND Appropriateness methodology. Separately, 25 women with limited health literacy (patients) and 20 primary care providers (PCPs) from outpatient clinics at a Boston‐based safety net hospital completed interviews exploring mammography‐related informational needs. To identify areas where stakeholder perspectives converged or diverged from each other, we conducted a qualitative synthesis using a constant comparison technique. Codes were developed and compared: (1) at the level of the individual interview; (2) within stakeholder groups; and, (3) across stakeholder groups. Population Studied: Eight experts participated in the Delphi panel. Participants had an advanced degree (MD, PhD), > 3 years of either professional, clinical or research experience, and content expertise in breast cancer screening, health literacy, or DA design. Patients included mammography‐eligible, primary care patients ages 40–54 with upcoming visits, and limited health literacy as defined by a score of <7 on the Health Literacy Skills Instrument‐10. PCPs included physicians and nurse practitioners in family medicine or general internal medicine clinics. Principal Findings: In the multi‐stakeholder synthesis, four themes regarding informational needs were identified related to: (a) the benefits and harms of screening, (b) different screening modalities, (c) the experience of mammography, and (d) communication about breast cancer risk. Convergence occurred around personal risk information, with all stakeholders describing it as important. Divergence occurred within the other three themes. Patients viewed pain as the primary harm, while PCPs and experts emphasized false positives as the primary harm. Process information about the mammography experience was critical to patient decisions; Experts and PCPs described process as less relevant. Patients valued breast self‐exam information, while PCPs and experts did not since self‐exams have been shown to be ineffective. Conclusions: While experts and PCPs prioritized providing evidence‐based options only, emphasized technology‐related harms, and downplayed the relevance of delivering mammography process information, patients were more concerned about pain, breast self‐exam (which is not supported by evidence), and viewed process information as fundamental to their decision‐making. These differences indicate opportunities to address patient‐identified unmet informational needs in breast cancer screening DAs. Implications for Policy or Practice: Evidence and guidance to advance best practices in integrating diverse and potentially divergent input across groups in DAs is warranted. Greater integration of patient voices, especially of those who are underserved, requires additional efforts to address patients' informational needs, which may differ from expert‐ and PCP‐defined priorities. Primary Funding Source: National Institutes of Health.